2013
DOI: 10.1182/blood-2012-07-440487
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F activates Lu/BCAM-mediated red cell adhesion in polycythemia vera through an EpoR-independent Rap1/Akt pathway

Abstract: Key Points• In polycythemia vera RBCs, JAK2V617F is able to activate an adhesion molecule through a Rap1/Akt pathway, despite the absence of EpoR.• In polycythemia vera, the abnormal adhesion of RBCs to laminin is due to the phosphorylation of Lu/BCAM by a JAK2V617F/Rap1/Akt pathway.Polycythemia vera (PV) is characterized by an increased RBC mass, spontaneous erythroid colony formation, and the JAK2V617F mutation. PV is associated with a high risk of mesenteric and cerebral thrombosis. PV RBC adhesion to endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
72
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 48 publications
(63 reference statements)
2
72
0
2
Order By: Relevance
“…Recently, we showed that this abnormal adhesion stems from JAK2V617F-mediated Lu/BCAM activation through a Rap1/Akt signaling pathway [5]. Blocking this pathway by JAK2 specific inhibitors led to significant decrease of PV RBC adhesion [5]. Here, we extended our findings by a quantitative analysis to determine the relationship between the rate of RBC adhesion to laminin and the JAK2V617F allele burden.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…Recently, we showed that this abnormal adhesion stems from JAK2V617F-mediated Lu/BCAM activation through a Rap1/Akt signaling pathway [5]. Blocking this pathway by JAK2 specific inhibitors led to significant decrease of PV RBC adhesion [5]. Here, we extended our findings by a quantitative analysis to determine the relationship between the rate of RBC adhesion to laminin and the JAK2V617F allele burden.…”
supporting
confidence: 62%
“…1B). These results indicated that Lu/ BCAM expression alone did not account for the variability of PV RBC adhesion, in accordance with the role of Lu/BCAM phosphorylation in the adhesion of PV RBCs to laminin [5].…”
supporting
confidence: 56%
See 2 more Smart Citations
“…13 In PV, the JAK2V617F mutation causes activation of the RAP1/Akt signaling pathway that eventually leads to Lu/BCAM activation through phosphorylation. 14,15 Upon phosphorylation, Lu/BCAM is believed to detach from the underlying spectrin network 16,17 and thus to more easily cluster upon ligation of laminina5. Although both Lu and Lu(v13) contain the cytoplasmic motif that interacts with the underlying spectrin network, 17 only the Lu cytoplasmic tail seems to contain phosphorylation sites that modulate this interaction.…”
Section: Introductionmentioning
confidence: 99%